Tackling neurodegenerative diseases with genomic engineering: A new stem cell initiative from the NIH - Ramos, Daniel M; Skarnes, William C; Singleton, Andrew B; Cookson, Mark R; Ward, Michael E (Neuron (Cambridge, Mass.), 2021)
The iPSC Neurodegenerative Disease Initiative (iNDI) is the largest-ever iPSC genome engineering project. iNDI will model more than 100 mutations associated with Alzheimer's disease and related dementias (ADRD) in isogenic iPSC lines. Resulting cell lines and phenotypic datasets will be broadly shared.